Toward More Scalable Processes for Perovskite Solar Cells: A Comparison Between Planar and Mesoporous Architectures - Fatou Diaw Ndiaye; Lara Perrin; Maria Bernechea; Lionel Flandin; Emilie Planes (Nano Select)
ABSTRACT Developing perovskite solar cells (PSCs) under ambient conditions remains challenging due to the material's sensitivity to oxygen and moisture. This study presents two types of PSCs fabricated entirely under ambient atmospheric conditions using different deposition techniques: spin coating and drop casting. Spin‐coated cells were produced with a compact planar structure (C‐PSC), while drop‐cast cells utilized a mesoporous architecture (M‐PSC), which not only lowers manufacturing costs but also reduces the environmental impact by limiting perovskite exposure to air during processing. Both architectures employed a CH3NH3PbI3 perovskite layer, stabilized with either chloride anion (Cl−) or ammonium valeric acid cation (AVA+) additives to enhance film stability. The maturation process of fresh cells was also investigated, revealing that M‐PSC devices benefited from increased photovoltaic activity postmaturation. Functional cells were achieved, with the C‐PSC_Cl devices reaching nearly 13% power conversion efficiency (PCE) and M‐PSC_AVAI_m devices attaining a PCE of 10.7%. The M‐PSCs also showed larger active areas and more consistent performance, underscoring their reproducibility and suitability for scaling. This study provides valuable insights into cost‐effective and environmentally sustainable fabrication methods for PSCs, offering promising pathways for the large‐scale manufacturing and deployment of PSC technologies.